Iron biomarkers in men with infertility are associated with sperm DNA hydroxymethylation and cumulative live birth rates: a prospective study - Georges Raad; Fatima Husseiny; Zalihe Yarkiner; Valerie Grandjean; Marwa Bazzi; Marilyne Rizk; Fadi Fakih; Youmna Mourad; Chadi Fakih (Journal of Translational Medicine)
Abstract Background Pregnancy rates after intracytoplasmic sperm injection (ICSI) could be influenced by sperm quality. Maintaining iron homeostasis is crucial for both sperm quality and the activity of ten-eleven translocation (TET) enzymes. TETs play a role in DNA chemical modifications. However, the impact of iron biomarkers on the sperm DNA chemical modifications and pregnancy outcomes has not been explored. This prospective study aimed to assess whether iron biomarkers in men from infertile couples were associated with global DNA hydroxymethylation (5-hmC) in spermatozoa and cumulative live birth rates (CLBR). Methods Semen and blood samples were collected from 60 infertile men undergoing ICSI cycles with their female partners, alongside medical histories and CLBR outcomes. Serum and seminal fluid levels of iron, transferrin, and total iron binding capacity (TIBC) were measured, and sperm global DNA 5-hmC was quantified using ELISA-based colorimetric assays. Results 5-hmC levels in spermatozoa were positively correlated with serum iron (R = 0.29; p = 0.04), serum TIBC (R = 0.29; p = 0.04), and seminal fluid iron (R = 0.30; p = 0.04). Univariate analysis showed that a 1 µg/dl increase in seminal fluid or serum iron was associated with a 0.001% rise in 5-hmC (p < 0.05), and each unit increase in serum TIBC led to a 0.001% rise in 5-hmC (p = 0.03). Multivariate regression confirmed that higher serum TIBC levels were significantly associated with increased 5-hmC (%) (p = 0.02). Additionally, multivariate analysis revealed that a 1 µg/dl increase in seminal fluid iron was associated with a 1.016% rise in CLBR (p = 0.0009), while a 1 mg/dl increase in seminal fluid transferrin was associated with a 3.754% decrease in CLBR (p = 0.04). Conclusion Serum TIBC is positively associated with sperm 5-hmC, while seminal iron shows a positive and transferrin a negative association with CLBR.